Squamous cell carcinoma: pain as a clue to increased tumour diameter, increased invasion depth, the grade of differentiation, acantholysis and perineural invasion. (18th September 2019) - Pyne, J. H.; Myint, E.; Clark, S. P.; Clifopoulos, C.; Fishburn, P.; Gorji, M.; Hou, R.
Summary: Background: Pain may be associated with actinic keratosis (AK), intraepidermal carcinoma (IEC) and invasive squamous cell carcinoma (SCC), which may all display high‐risk features. Aim: To examine variation in pain frequency associated with these three conditions, and assess their invasive SCC surface diameter, invasion depth, grade of differentiation, presence of acantholysis and perineural invasion (PNI). Methods: Pain was prospectively recorded for consecutive cases of AK, IEC and SCC from three institutions in Australia during the period 2016–2018. Results: Pain with palpation was recorded with 15.8% of AK ( n = 30/190), 15.1% of IEC ( n = 345/299) and 29.0% invasive SCC ( n = 247/853). Pain without palpation was respectively 1.1% (2/190), 4.0% (12/299) and 6.7% (57/853). Invasive SCC with increased surface diameters and deeper invasion recorded increased pain frequency. Pain did not vary significantly by the grade of differentiation in males. In females, well‐differentiated SCC recorded more pain (45.4%; n = 473) than poorly differentiated SCC (9.1%; n = 11). Acantholytic SCC recorded more pain 48.7% ( n = 29) than nonacantholytic SCC 35.2% ( n = 824). Three out of five cases of PNI recorded pain. Pain intensity was not recorded, which was a limitation. Conclusion: Pain presence increases from AK to invasive SCC. Pain was more frequent in invasive SCC with increased surface diameter, deeper invasion, acantholysis and PNI. Pain frequency did not vary between the grades of differentiation in males. In females, pain was less frequent in poorly differentiated than in well‐differentiated SCC.